SISTEM PEMANTAU RUANG JARAK JAUH DENGAN SENSOR PASSIVE INFRARED BERBASIS MIKROKONTROLER AT89S52 - Albert Gifson; Slamet Slamet (Universitas Ahmad Dahlan, 2009)
This research describes about the design of the room detection system using a Passive Infrared sensors (PIR) controlled by Microcontroller AT89S52 for remote control application. The output of the PIR is a low logic when it captures the heat waves of the human body. The output PIR is connected to the port 1.7 on Microcontroller in high logic. The maximum distance is 5 meters for the sensor to detect an object. When there is a signal sent by PIR, the Microcontroller processes the data and activates the buzzer to beep and the stepper motor to stop. Microcontroller also sends data through the RS-232 that continues a signal to the personal mobile phone. In order that the message is able to be sent, then first, messages must be programmed and stored in the Microcontroller AT89S52. The average message delivery time is 8.8 seconds. The recipient can turn the alarm of system on or off by a missed call.